2018
DOI: 10.1186/s12916-018-1175-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult height and risk of 50 diseases: a combined epidemiological and genetic analysis

Abstract: BackgroundAdult height is associated with risk of several diseases, but the breadth of such associations and whether these associations are primary or due to confounding are unclear. We examined the association of adult height with 50 diseases spanning multiple body systems using both epidemiological and genetic approaches, the latter to identify un-confounded associations and possible underlying mechanisms.MethodsWe examined the associations for adult height (using logistic regression adjusted for potential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 58 publications
9
87
0
2
Order By: Relevance
“…We further build on those prior findings using the MR framework, considering both summary-level and individual-level genetic data, examining genetic variants associated with height and atrial fibrillation to provide a causal estimate for the effect of increasing height on risk of atrial fibrillation. Our population-level MR analysis reinforces a prior MR estimate for association between increasing height and atrial fibrillation (OR 1.33; 95% CI 1.26 to 1.40) using updated GWAS summary statistics for height and atrial fibrillation [9]. By including a large multiethnic study of atrial fibrillation, we increase the generalizability of the prior MR findings, which were limited only to white participants of the UK Biobank.…”
Section: Plos Medicinesupporting
confidence: 63%
See 1 more Smart Citation
“…We further build on those prior findings using the MR framework, considering both summary-level and individual-level genetic data, examining genetic variants associated with height and atrial fibrillation to provide a causal estimate for the effect of increasing height on risk of atrial fibrillation. Our population-level MR analysis reinforces a prior MR estimate for association between increasing height and atrial fibrillation (OR 1.33; 95% CI 1.26 to 1.40) using updated GWAS summary statistics for height and atrial fibrillation [9]. By including a large multiethnic study of atrial fibrillation, we increase the generalizability of the prior MR findings, which were limited only to white participants of the UK Biobank.…”
Section: Plos Medicinesupporting
confidence: 63%
“…Even with treatment, affected individuals are at risk of cardioembolic stroke, heart failure, and death [2]. Height has been identified as a risk factor for a number of cardiometabolic diseases, including coronary artery disease, atrial fibrillation, and venous thromboembolism [9,10]. The relationship between height and atrial fibrillation in particular has been identified in large observational studies, with greater height strongly associated with increased risk of atrial fibrillation [4,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from observational studies suggests that height is associated with different disease outcomes 14 . Other studies have tried to elucidate this inverse association by using a twin design 5 or Mendelian randomisation approaches 4,6,7 . A decrease of one standard deviation in genetically determined height (~6.5 cm) has been associated with a 13% higher risk of coronary artery disease (CAD) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44] Besides, ve possible shared biologic pathways (ERK5 signaling, Wnt/β-catenin signaling, androgen signaling, role of Oct4 in mammalian embryonic stem cell pluripotency, Growth hormone signaling) between adult height and AF have been identi ed in a prior study. [45] In addition, this association appears to be in part mediated via body mass as well. In the Women's Health Study, additional adjustment for body mass further attenuated the association between BW and AF risk.…”
Section: Discussionmentioning
confidence: 99%